Assessing Land Use and Land Cover Change in the Keta Municipality of Ghana Using Remote Sensing - Peters, M.K. (University of Ghana, 2019)
Coastal areas around the world are increasingly facing devastating disasters due to land use and land cover changes. Same can be said of Keta Municipality which experiences series of challenges such as unplanned urbanisation, intensive agriculture, flooding and coastal erosions. To design better solutions to these recurring problems, there is the need to understand the landscape and its interaction with its inhabitants. To achieve this, this study employed remote sensing techniques by acquiring historically sensed data of 1991, 2005 and 2018. The focus of the study was to determine the various land use and land cover types that exist in the study area and also examine the changes that have occurred over the years. The study established that the Keta Lagoon remained the most dominant land cover from 1991 to 2018 occupying 267.5km2 and 282.01km2 respectively. Wetlands which are known to be flood protection agents have however reduced from 182.33 km2 to 135.11 km2 from 1991 to 2018. Agricultural activities have been on the rise in the Municipality and is evident in the surface area farmlands covered by the year 2018. This rise may be understood to keep up with the population growth in the municipality. However, the conversion of wetland areas into agricultural lands has exposed human settlements to issues such as floods and coastal erosions. In view of these revelations, there is the need for intensification of education on the benefits of wetlands in the protection of lives and properties in the area. In the short term, farming activities need to be regularised by the local government so that wetlands will be allowed to regenerate.
MPhil.
Keywords: Land Cover Change; Land Use; Keta Municipality